INFLUENCES OF MANURE AND BIOCHAR ON BIOMASS YIELD AND NUTRIENT VALUE OF PENNISETUM PURPUREUM CV. MOTT GROWN ON POST-NICKEL-MINING SOIL - W. Kurniawan; Hardianto; A. Ramdani; A. Bain; T. Bachtiar; T. Wahyono (Journal of Animal and Plant Sciences, 2022)
The objectives of this study were to determine the effects of biochar and manure additions to growth performance, nutrient value, in vitro digestibility, and rumen fermentation characteristics of Pennisetum purpureum cv. Mott grown in soil remaining after nickel-mining activities. The goat manure and iron wood biochar were used in this study. Treatments were arranged 4 x 2 factorially in a completely randomized block design. The factors were four levels of biochar (0, 5, 10, and 15 metric ton/ha) and two levels of manure (0 and 10 metric ton/ha). The plants were harvested at 70 days after sowing (first harvest), 128 days (first ratoon) and 193 days (second ratoon). Results showed that at first and second ratoon, plant height and tillering number were increased after 5 metric ton/ha biochar and 10 metric ton/ha manure additions (p < 0.05). Manure treatment resulted in higher crude protein content (p < 0.05) than controls at first and second ratoon stages. Combinations of biochar (p < 0.01) and manure (p = 0.09) improved in vitro gas production from the insoluble fraction (b). The study concludes that treatment with 5 metric ton/ha biochar and 10 metric ton/ha manure fertilizers on post-nickel-mining soil increases tillering number, height, CP content and in vitro digestibility of P. purpureum cv. Mott at ratoon stages.
Keywords: Biochar; manure; nutrient value; Pennisetum purpureum cv. Mott; post-mining